2018
DOI: 10.1007/s00415-018-8951-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Duodopa® effects on quality of life of patients with advanced Parkinson’s disease and their caregivers

Abstract: The gold standard of treatment in Parkinson's disease (PD) is levodopa/carbidopa whose long-term use induces motor and non-motor fluctuations and dyskinesias. Continuous infusion of intrajejunal levodopa/carbidopa intestinal gel (Duodopa) reduces motor and non-motor symptoms and dyskinesias, and improves the quality of life of patients. The aim of this open observational prospective study was to evaluate the impact of Duodopa on conditions of PD patients and caregivers, and their quality of life. We enrolled 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 52 publications
1
30
0
1
Order By: Relevance
“…2 It has recently been reported that after 6 months of LCIG treatment there was a significant improvement of anxiety, depression, level of care burden and QoL, especially in the domains related to social life, 2908 vitality and mental health compared to baseline, even if no significant relationship was found between these factors and the burden. 17 In another study, a parallel trend between caregivers' QoL, depression, burden, sleep and patients' QoL, depression and sleep has been observed. 28 We found it noteworthy in our study, that although more than 50% of the patients had sleep disturbances and approximately one third of the patients had a feeling of depressed mood, the intensity of the caregiver's burden was mild or moderate.…”
mentioning
confidence: 86%
“…2 It has recently been reported that after 6 months of LCIG treatment there was a significant improvement of anxiety, depression, level of care burden and QoL, especially in the domains related to social life, 2908 vitality and mental health compared to baseline, even if no significant relationship was found between these factors and the burden. 17 In another study, a parallel trend between caregivers' QoL, depression, burden, sleep and patients' QoL, depression and sleep has been observed. 28 We found it noteworthy in our study, that although more than 50% of the patients had sleep disturbances and approximately one third of the patients had a feeling of depressed mood, the intensity of the caregiver's burden was mild or moderate.…”
mentioning
confidence: 86%
“…Specifically, mood, neuropsychiatric symptoms, sleep problems, fatigue, and pain were more severe in patients with 5-2-1 positive criteria and the percentage of patients with severe to very severe NMS burden was the double in this group compared to those patients with negative criteria. On the other hand, some studies have shown improvement in the caregiver status of patients with advanced PD after starting some second-line therapies [29,30]. An overburdened caregiver cares less which contributes to a worse QoL of the patient, so it is important to identify the problem and take action.…”
Section: Discussionmentioning
confidence: 99%
“…Hinsichtlich der Bedeutung medikamentöser und invasiver Therapien auf die Betreuungsbelastung finden sich in der Literatur einerseits der Faktor Dosis der dopaminergen Therapie als Ausdruck der Krankheitsdauer und des Schweregrades der motorischen Symptomatik des Pfleglings als ein Belastungsfaktor [12,33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], andererseits einige medikamentöse Therapien, wie die Levodopa/Carbidopa intestinale Geltherapie (Duodopa), zu der in nichtkontrollierten Studien teilweise positive Effekte auf die Betreuungsbelastung festgestellt wurden [38,39] und die Palliativ-Betreuung [19,20,32]. Außerdem wurde in kontrollierten Therapiestudien mit Memantin und Donepezil bei Personen mit Parkinson-Demenz und Demenz mit Lewy-Körperchen sowie mit Rivastigmin bei apathischen depressions-und demenzfreien Parkinson-Pat.…”
Section: Literaturrecherche Und Analyseunclassified